2010
DOI: 10.1002/ijc.25441
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR‐2 expression in carcinoid cancer cells and its role in tumor growth and metastasis

Abstract: Carcinoid tumors are slow growing and highly vascular neuroendocrine neoplasms that are increasing in incidence. Previously, we showed that carcinoid tumors express vascular endothelial growth factor receptor 2 (VEGFR-2) in the epithelial compartment of carcinoid tumor sections; yet, its role is not completely understood. The purpose of our study was to: (i) assess the expression of VEGFR-2 in the novel human carcinoid cell line BON, (ii) to determine the role of PI3K/Akt signaling on VEGFR-2 expression and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 47 publications
(157 reference statements)
2
47
0
Order By: Relevance
“…A high-molecular-weight band was visible on DNA gel electrophoresis, excluding DNA degradation. Short tandem repeat profiling using a Powerplex Kit (Promega) of BON-1 and QGP-1 gave results consistent with those obtained by the original group (Silva et al 2011) and the JRCB database, respectively, thus confirming the cell lines' identity.…”
Section: Cell Culture and Dna Isolationsupporting
confidence: 80%
“…A high-molecular-weight band was visible on DNA gel electrophoresis, excluding DNA degradation. Short tandem repeat profiling using a Powerplex Kit (Promega) of BON-1 and QGP-1 gave results consistent with those obtained by the original group (Silva et al 2011) and the JRCB database, respectively, thus confirming the cell lines' identity.…”
Section: Cell Culture and Dna Isolationsupporting
confidence: 80%
“…This change from prevascular hyperplasia to highly vascularized tumors has been referred to as the angiogenic switch (1). In recent years, several studies have reported expression of VEGFR1 as well as VEGFR2 on tumor cells (3)(4)(5). An intriguing finding related to tumor cell expression of Flt1 was the observation that VEGF secreted by tumor cells triggers tumor cell proliferation by binding Flt1 (6).…”
Section: Introductionmentioning
confidence: 99%
“…26,28 Moreover the VEGF receptor-2 (VEGFR-2) is also generally over-expressed also in gastro-intestinal carcinoid tumors and carcinoid cancers. 26,29 Thus, targeting these markers potentially arrest the NETs related-angiogenesis inducing, as a consequence, a tumor downstage and an improvement in PFS/ OS. 12,20,21 The present study is a systematic review and a meta-analysis of trials to assess the efficacy of targeted agents in patients with advanced NET.…”
Section: Discussionmentioning
confidence: 99%